Pengaruh Sistem Pengendalian Internal, Budaya Organisasi, Komitmen Organisasi, dan Penegakan Hukum terhadap Kecendrungan Kecurangan di Lembaga Perkreditan Desa, (Studi Kasus pada Kecamatan Sawan Kabupaten Buleleng) - Dewi, Kadek Hartani Graha; Dewi, Putu Eka Dianita Marvilianti (Jurnal Akuntansi Profesi, 2021)
This purposes of research is to know the effect of the internal control system, organizational culture, organizational commitment, and law enforcement on fraud tendency of LPD in Sawan District . This research apply quantitative research methods, by processing primary data. Sampling technique for determine of data source is purposive sampling method, and that involves LPD in Sawan District. Data source of this research was obtained by using a questionnaire, and then it is processed by using multiple linear analysis test in SPSS. The results of research is show that implementation of internal control system and law enforcement partially has a significant effect on fraud tendency of LPD in Sawan District. While, organizational culture and organizational commitment partially have no significant effect on fraud tendency of LPD in Sawan DistrictKeywords: internal0control0system, organizational0culture, organizational0commitment, law enforcement, fraud0tendency